TINDAK TUTUR DIREKTIF DAN TINDAK TUTUR EKSPRESIF PADA PODCAST VIDI PODHUB DALAM CHANNEL YOUTUBE DEDDY CORBUZIER - Hani Puja Kusuma; Achmad Wahidy; Yenny Puspita (Kampus Akademik Publiser, 2024)
This research describes Directive and Expressive Speech Acts on the Vidi Podhub Podcast on Deddy Corbuzier's YouTube Channel, because this research has never been carried out before. The aim of this research is to describe directive and expressive speech acts on the Vidi Podhub Podcast on Deddy Corbuzier's YouTube channel. In this study, researchers used pragmatic studies in directive and expressive speech acts. This type of research uses a qualitative descriptive method with data collection techniques using note-taking techniques. Based on the research results, 12 directive utterances and 29 expressive utterances were found. Between the two directive and expressive speech acts, expressive speech acts are more numerous and dominant because the host can appreciate, give a good impression and give praise to each guest star they invite.